Cost Management in Improving the Quality of Education at Tsanawiyah Madrasah in Sukabumi Regency - HU Badrusalam (Journal of Islamicate Studies, 2021)
The background of this research is that the education financing in Madrasah Tsanawiyah has not been able to improve the quality of education, presumably because cost management has not been implemented so that the quality of education and learning is still weak. The general objective of the study is to determine cost management in improving the quality of education at Madrasah Tsanawiyah in Sukabumi Regency and the specific objectives are to describe (1) planning, (2) organizing, (3) implementation, (4) supervision, (5) results, (6) constraints, and (7) solutions in cost management to improve the quality of education. The grand theory used is C. Benson's Educational Cost Management Theory. Using a qualitative approach, descriptive method with data collection techniques through interviews, observations, and documentation studies. The results of the study are as follows: (1) Cost planning in improving the quality of education in MTs at the beginning of the fiscal year begins with the preparation of the Madrasah Work Plan and Budget (RKAM) based on EDM to determine the priority scale of BOS/DIPA budget allocation according to the needs of the madrasa, (2) Organizing the cost of improving the quality of education in MTs is carried out by the Madrasah Boss Team. Both DIPA and BOS funds are allocated to finance activities to meet the 8 National Education Standards, (3) The implementation of costs in improving the quality of education at MTs is realized by financing educational activities as detailed in the RKAM according to the BOS Technical Guidelines that have been set, (4) Supervision of costs in improving the quality of education in MTs is carried out so that madrasas can manage finances properly, transparently, and accountably. Supervision is carried out through monitoring and evaluation activities (monev) from the Ministry of Religion and an audit team from the Inspectorate General of the Ministry of Religion, BPKP, and BPK, (5) The result of cost management in improving the quality of education in MTs is an increase in the quality of implementation and learning outcomes, (6 ) Constraints experienced include those related to sourcing, planning, organizing, implementing, and controlling costs, and (7) Solutions implemented by MTs to overcome obstacles experienced in cost management to improve the quality of education are efficient use of budgets and increased community participation. . The conclusion of the research is that cost management can improve the quality of education at Madrasah Tsanawiyah in Sukabumi Regency